STUDI DAMPAK SERTIFIKASI TERHADAP KINERJA MENGAJAR GURU MADRASAH - Suryadi Suryadi (Universitas Pendidikan Indonesia, 2011)
Purpose of doing of this study to know giving impact of educator certificate to teacher in each education ladder of madrasah public/private ( Ml, MTS, and MA). Solution is more focussed at performance to teach teacher madrasah which has owned educator certificate, achievement of student at madrasah which has owned teacher is certified, and construction program of teacher madrasah post certificated. Study about impact certificated to this madrasah teacher performance methodologically is done by using evaluation research method through step (1) formulation phase; ( 2) exploration and confirmation; ( 3) input and data processing; and (4) reporting. All the research phases done in range of time five months. Study stages;steps done that is: (1) specifies and defines study focus, ( 2) determines study focus indicator, ( 3) compilation of instalment, ( 4) data source stipulating, ( 5) data collecting, ( 6 data analysis, ( 7) validation result of data processing, and ( 8) compilation of report Kesimpulan result of study has not fully depicts comprehensive and hilly condition about impact of certificate to performance teachs teacher in area madrasah because location of study and number of responders still very limited.However, result of study has can give image of public which able to be made input to all policy taker in the management of certificate programe teacher in coming, and studies furthermore about impact to improvement of performance teachs teacher madrasah.